THE PRADAKON - Fendi Adiatmono; Arif Rivai (Balong International Journal of Design, 2018)
The essence of the Stone Age, mountain, and river heritage, has occupied an important role in culture. So far, it can reflect much of the trust and value of its people. Historical, aesthetic, anthropological, and symbolic studies of archaeological discoveries in the region have been able to reveal prehistoric culture. The focus of this section, especially how culture is developed, symbols are built and the appreciation of transmission of inheritance. It is related to the software and hardware of the royal government that was formed to be able to balance the mandate of the management of the land of the archipelago. In the field of history, aesthetics, anthropology, and symbols, the dimensions of life cycle are presented as dialectical patterns of view. It is found that small, large, and representative entities are patterns of view that have been applied dynamically to everyday life. Through a comprehensive approach to the history of society and artevactual, apart from its constitutional history, the authors emphasizes the analysis of social formation by looking at the processes occurring within societies with broader disciplinary comparations. Through the applied method of psychological Sunan Bonang, the Indonesian people are inspired and can have a good system of anthropological and psychological intelligence. Research of this book uses theory and method which are relevant with object and subject matter. So the context that is built into legitimate, in text, oral and visual, both present (represented by Arif Rivai Rumin's work) and past (pradakon Majapahit, Ancient Mataram, Pajajaran, Kuningan, Jambi, and Padang) have been used as reconstruction. The content of the study and his work inspires the public's sensitivity in formulating nationality through the compilation of software and hardware in a more integral way. The ultimate goal is the point of awareness, which makes filters and counters a global power that seeks to make all the people of Indonesia. Keywords: pradakon, intellectual people of IndonesiaKeywords: pradakon, intellectual people of Indonesia